Layered Au-Pd-Au nanorod catalysts: Pd-layer thickness effects on catalyst performance. (7th June 2019) - Laghrissi, Ayoub; Es-Souni, Mohammed
Abstract: Au/Pd/Au and Au/Pd layered nanorods (NR) with different Pd thickness, down to 15 nm, are electrodeposited in Si-supported porous anodized aluminum thin film templates. These structures are, in contrast to Au-Pd core-shells, mechanically relaxed, so that chemical and electronic interaction effects between Au and Pd are expected to predominate in controlling their performance in the electrooxidation of formic acid. The XRD results are conclusive about the formation of pure metal layers, but a corrugated Au/Pd interface is revealed by scanning electron microscopy. The CV behavior of the different structures shows that the PdO reduction peak is shifted towards more noble values as the Pd thickness decreases. Regarding the electrocatalytic oxidation behavior there is a substantial increase in performance with decreasing Pd-layer thickness. It is further shown that the Au/Pd/Au nanostructures perform better than the Au/Pd bilayer structure for the same Pd layer thickness. Also the long term behavior is improved. Both CV and electrocatalytic behaviors are discussed in terms of interfacial intermixing between Pd and Au at the nanoscale and a higher interface contribution for thinner Pd layers. Graphical abstract: Image 1 Highlights: Supported Au/Pd/Au Nanorod arrays with different Pd-thicknesses are prepared. The CV behavior suggests the existence of near interface alloys. Thin Pd-layers show a better performance and durability. Near interfacial effects are rationalized using Density functional theory calculations. The interfacial Au atoms are thought to catalyze CO oxidation and improve long-term stability.